Cooking oil waste as corrosion inhibitor for mild steel in 1M HCl solution / Nadiah Hanim Mohd Noordin - Mohd Noordin, Nadiah Hanim (Institute of Graduate Studies, UiTM, 2016)
Metals generally tend to move to its original state by corrosion process. Mild steel is an alloy form of iron, which undergoes corrosion easily in acidic medium. Palm cooking oil waste (PCOW) was introduced as a new organic corrosion inhibitor due to its fatty acids content. PCOW was soluble and stable in water at pH 11, 50˚C with ratio 75: 25 oil to water respectively. The reaction between fatty acid in PCOW with NaOH was produced surfactants which solubilise oil in water and produce o/w emulsion. The fatty acids in PCOW were further reacted with diethylene triamine to increase the adsorption process of PCOWAI on steels surface. The inhibition behaviour of palm cooking oil waste inhibitor (PCOWAI) on mild steel in 1M HCl as corrosive solution containing different concentrations of PCOWI at 299, 323 and 343K was investigated by weight loss and potentiodynamic polarization and electrochemical impedance spectroscopy. It has been observed that corrosion rate decreases and inhibition efficiencies and surface coverage degree increases with increasing in PCOWI concentration. The maximum inhibition efficiency 100% was observed in the presence of 0.25 M inhibitor at 299K. The recorded potentiodynamic polarization data indicated the basic modification of steel surface as a result in a decrease in the corrosion rate…